Lithium battery recycling material powder as well as preparation method and application thereof

By preparing lithium battery recycling material powder with suitable separation index, and using processes such as photocatalytic oxidation treatment, flash drying and heat treatment, the problems of low metal leaching rate and low separation efficiency in lithium battery recycling are solved, and efficient metal recycling and material regeneration are achieved.

CN119839285AActive Publication Date: 2025-04-18GUANGDONG BRUNP RECYCLING TECH CO LTD

Patent Information

Application Number
CN202510324106.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2025-04-18
Estimated Expiration
2045-03-19

AI Technical Summary

Technical Problem

In the existing lithium battery recycling technology, the metal leaching rate during the hydrometallurgy process is low and the separation efficiency of positive and negative electrode materials is not high, resulting in high recycling costs and product performance not meeting the standards.

Method used

By providing a lithium battery recycling material powder, the powder containing metal compound powder and elemental carbon material, the separation index S meets 0.15m2/kg≤S≤43m2/kg, combined with the processes such as photocatalytic oxidation treatment, flash drying and heat treatment, lithium battery recycling material powder with excellent physicochemical properties is prepared.

Benefits of technology

The metal leaching rate of lithium battery recycling material powder in the hydrometallurgy process and the separation efficiency of positive and negative electrode materials are improved, the recycling cost is reduced, and the performance and application value of the product are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_13
    Figure SMS_13
  • Figure SMS_14
    Figure SMS_14
  • Figure SMS_15
    Figure SMS_15
Patent Text Reader

Abstract

The invention discloses lithium battery recycling material powder as well as a preparation method and application thereof, and relates to the technical field of battery recycling. The lithium battery recovery material powder comprises metal compound powder and an elemental carbon material, and the metal compound powder comprises at least one of the following elements: lithium, nickel, cobalt, manganese and iron; the separation index S of the lithium battery recovery material powder is greater than or equal to 0.15 m < 2 > / kg and less than or equal to 43 m < 2 > / kg, S = WDOC * BET, WDOC refers to the mass percent of soluble organic carbon in the lithium battery recovery material powder, and the soluble organic carbon refers to organic carbon which can be dissolved or dispersed in an aqueous solution with the pH value of 1-14; bET refers to the specific surface area of the lithium battery recovery material powder. The separation efficiency is high when the positive electrode material and the negative electrode material in the lithium battery recycled material powder are separated, and when the lithium battery recycled material powder is subjected to hydrometallurgy to extract valuable metal, the good metal leaching rate is achieved in the acid leaching stage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery recycling, and in particular to a lithium battery recycling material powder and a preparation method and application thereof. Background Art

[0002] With the rapid development of science and technology, the market demand for new energy, especially new energy vehicles, continues to expand. Lithium batteries, as their core components, have been widely used. However, the subsequent problem of retired battery disposal has become a bottleneck in the development of the industry. Lithium battery recycling material powder (black powder, Black Mass) recycling technology came into being, recycling and reusing the valuable metals and other materials in waste batteries, realizing the green transformation of waste into treasure. Lithium battery recycling material powder mainly comes from the disassembly, crushing, screening and other processes of waste lithium batteries. The main components include valuable metals such as lithium, cobalt, nickel, and manganese, and non-metallic materials such as carbon powder and plastic.

[0003] At present, the mainstream methods or research directions for the recycling and reuse of black powder include pyrometallurgy, hydrometallurgy, direct regeneration, etc. Pyrometallurgy refers to a metallurgical method that separates metals from other impurities through high-temperature smelting and reduction reactions to obtain metal elements. This method has a low waste utilization rate and high energy consumption and pollution. It can only obtain metal alloys and is gradually being eliminated; hydrometallurgy refers to ionizing metal elements, and then separating and enriching metals through precipitation, electrolysis, extraction, ion exchange and other technologies, and finally recovering the target metal in the form of a certain chemical state. This method can obtain relatively pure metal compounds and can be directly used to prepare electrode materials. It is the current mainstream recycling method; direct regeneration refers to solving the failure problem of materials in a targeted manner without destroying the inherent structure of the material, realizing structural regeneration, and thus restoring the electrochemical activity of the material. This method has the lowest recycling cost and the lowest pollution in the recycling process, but the regeneration cost is high and the performance of the recycled material still does not meet the application requirements.

[0004] In the hydrometallurgical process, acid leaching is usually used to ionize metal elements. The acid leaching process requires the addition of hydrogen peroxide to promote the dissolution of metal ions, which will produce a large number of bubbles. On the one hand, when the acid leaching solution contains dissolved organic carbon (DOC), these DOC are equivalent to surfactants, which will make it difficult to eliminate the bubbles and even cause bubbling, greatly reducing the leaching efficiency. On the other hand, when the bubbles float to the liquid surface, they will take away the black powder particles at the bottom of the kettle. When the porosity of the black powder particles is large (that is, the density is low), they tend to float on the liquid surface, resulting in a decrease in leaching efficiency.

[0005] Direct regeneration requires the positive electrode material and the negative electrode material in the black powder to be recycled separately. Therefore, the positive electrode material and the negative electrode material in the black powder need to be effectively separated without destroying their inherent structure. The basis of separation is the difference in water wettability and density between the two. The organic matter remaining in the black powder and coated on the surface of the positive electrode material and the negative electrode material particles will reduce the difference in water wettability between the two. If the porosity of the black powder particles is too high, the higher the degree of deviation of the positive electrode material and / or the negative electrode material from its true density, the greater the difficulty of separation using density difference, thereby reducing the sorting effect.

[0006] In the process of obtaining black powder by treating battery or electrode waste by physical or / chemical methods, it is of great significance to regulate the physicochemical properties of the black powder (such as organic matter content, specific surface area, particle size, etc.) to obtain black powder with good positive / negative electrode material separation effect and wet leaching efficiency in order to achieve black powder recovery and reuse.

[0007] In view of this, the present invention is proposed. Summary of the invention

[0008] The purpose of the present invention is to provide a lithium battery recycling material powder, aiming to improve the metal leaching rate in the hydrometallurgical process and the separation efficiency of the positive and negative electrode materials in the regeneration process.

[0009] The present invention is achieved in that: In a first aspect, the present invention provides a lithium battery recycling material powder, comprising a metal compound powder and a single carbon material, wherein the metal compound powder comprises at least one of the following elements: lithium, nickel, cobalt, manganese and iron; and the separation index S of the lithium battery recycling material powder satisfies 0.15m 2 / kg≤S≤43m 2 / kg, where S=W DOC ×BET, W DOC It refers to the mass percentage of soluble organic carbon in the lithium battery recycling material powder; the soluble organic carbon refers to the organic carbon that can be dissolved or dispersed in an aqueous solution with a pH of 1 to 14; BET refers to the specific surface area of ​​the lithium battery recycling material powder, in m 2 / g.

[0010] In some embodiments, the lithium battery recycled material powder satisfies at least one of the following characteristics 1 to 4: Feature 1: When the pH of the aqueous solution is ≤3, the separation index S of the lithium battery recycling material powder meets 2m 2 / kg≤S≤24m 2 / kg; Feature 2: When the pH of the aqueous solution is ≥10, the separation index S of the lithium battery recycling material powder meets 13m 2 / kg≤S≤40m2 / kg; Feature 3: W of lithium battery recycling material powder DOC Less than or equal to 15‰; Feature 4: BET of lithium battery recycling material powder meets 1m 2 / g≤BET≤15m 2 / g.

[0011] In some embodiments, the iron content of the lithium battery recycling material powder is 10% to 30% by mass, and the BET of the lithium battery recycling material powder is 10 to 15 m 2 / g.

[0012] In some embodiments, the mass percentage of cobalt element in the lithium battery recycling material powder is 1% to 50%, and the BET of the lithium battery recycling material powder is 1 to 3 m 2 / g.

[0013] In some embodiments, the Dv50 of the lithium battery recycled material powder is 0.6-16 μm.

[0014] In some embodiments, the Dv10 of the lithium battery recycled material powder is 0.1-1.5 μm.

[0015] In some embodiments, the Dv10 of the lithium battery recycled material powder is 0.5-5.2 μm.

[0016] In some embodiments, the lithium element mass percentage of the lithium battery recycled material powder is 0-10%.

[0017] In a second aspect, the present invention provides a method for preparing the lithium battery recycling material powder in any of the above embodiments, comprising the following steps: Provide lithium battery recycling crude materials including negative electrode materials, positive electrode materials and organic matter; The recycled raw material of lithium battery is subjected to photocatalytic oxidation treatment to obtain a photo-treated intermediate; flash drying the light-treated intermediate to obtain a dry intermediate; heat-treating the dried intermediate to obtain a heat-treated intermediate; The material is cooled to below 20° C. in an inert atmosphere, crushed and sieved to obtain lithium battery recycling material powder.

[0018] In some embodiments, the positive electrode material includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium iron phosphate.

[0019] In some embodiments, the negative electrode material includes graphite.

[0020] In some embodiments, the organic matter includes a polymer compound obtained by reacting a carbon-carbon unsaturated bond and an organic solvent, the polymer compound includes but is not limited to at least one of polyvinylidene fluoride PVDF, polyacrylonitrile PAN, polyacrylic acid PAA, polyethylene PE and polypropylene PP, and the organic solvent includes but is not limited to at least one of ethylene carbonate, propylene carbonate, butylene carbonate, pentyl carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate and ethyl methyl carbonate.

[0021] Photocatalytic oxidation treatment refers to ultraviolet light irradiation of lithium battery recycled raw materials in an oxygen-containing or / and water-containing environment in the presence of a photocatalyst; in some embodiments, the photocatalyst includes at least one of titanium dioxide and zinc oxide; preferably, the photocatalyst is anatase titanium dioxide; preferably, the particle size of the photocatalyst is less than 500nm and is supported on at least one of the following carriers: aluminum foil, ceramic, glass, silica, molecular sieve and sieve, in order to facilitate the separation of the phototreatment intermediate and the photocatalyst.

[0022] In some embodiments, the ultraviolet light irradiation conditions include: the light wavelength is 200-400 nm, and the irradiation time is 5-15 h.

[0023] In some embodiments, the ambient humidity of the photocatalytic oxidation treatment is maintained at 60% to 100%, and the ambient oxygen content is maintained at above 30vt%.

[0024] In some embodiments, the inlet air temperature of the flash drying is 200-400° C., the outlet air temperature is 100-200° C., the rotation speed is 10-30 Hz, and the feed frequency is 10-30 Hz.

[0025] In some embodiments, the heat treatment is performed under negative pressure, at a temperature of 350°C to 500°C, a pressure of -0.01 to -0.05 MPa, and a time of 0.5 to 1.5 h.

[0026] In some embodiments, the cooling rate is 1-6°C / min.

[0027] In some embodiments, the particle size of the lithium battery recycled coarse material is less than 1 cm.

[0028] In some embodiments, the lithium battery recycling crude material is obtained by crushing the battery waste by mechanical means such as disassembly, stamping, grinding, and shearing.

[0029] In some embodiments, battery waste includes, but is not limited to, used batteries, used battery cells, used battery rolls, pole piece waste, and unqualified batteries on a production line.

[0030] In some embodiments, the light portion of battery waste, such as plastic, aluminum foil, copper foil, etc., is removed by, for example, air separation, screening, density sorting, optical sorting, etc.

[0031] In some embodiments, the larger parts of the battery waste, such as the casing, wires, and sealing plates, can be separated by manual or automatic sorting. For example, the magnetic parts can be separated by a magnetic separator, and the non-magnetic metals can be separated by an eddy current separator.

[0032] In a third aspect, the present invention provides an application of lithium battery recycled material powder in any of the above embodiments.

[0033] The powder of lithium battery recycled material is applied to hydrometallurgy, and the hydrometallurgy step comprises: dispersing the powder of lithium battery recycled material in an acid solution to obtain an acid leaching solution containing metal ions.

[0034] In some embodiments, the post-acid leaching solution is subjected to steps including but not limited to impurity removal, extraction, precipitation and drying to obtain a product enriched in valuable metal elements, wherein the valuable metal elements include at least one of nickel, cobalt, manganese, lithium and iron.

[0035] In some embodiments, the post-acid leaching solution is subjected to steps including but not limited to impurity removal, extraction, etc. to obtain an aqueous solution enriched with metal salts; the metal salts include at least one of nickel salts, cobalt salts, manganese salts and lithium salts.

[0036] In some embodiments, the post-acid leaching solution is subjected to steps including but not limited to impurity removal, precipitation, carbonization, drying, etc. to obtain lithium carbonate.

[0037] The lithium battery recycled material powder is used for positive electrode material regeneration, and the steps include: using flotation separation method to enrich the positive electrode material in the lithium battery recycled material powder, adding lithium to calcine the positive electrode material to obtain regenerated positive electrode material.

[0038] Lithium battery recycled material powder is applied to graphite recycling, and the steps include: using flotation separation method to enrich graphite in lithium battery recycled material powder, and recycling the graphite.

[0039] In some embodiments, graphite is thermally treated to obtain a regenerated negative electrode material.

[0040] In some embodiments, graphite is used to prepare graphene.

[0041] The present invention has the following beneficial effects: The present invention provides a lithium battery recycling material powder, wherein the product of the soluble organic carbon content and the specific surface area of ​​the lithium battery recycling material powder satisfies an appropriate range, and the lithium battery recycling material powder within this range has a high separation efficiency when separating positive electrode materials and negative electrode materials; and when applied to hydrometallurgical extraction of valuable metals, has a good metal leaching rate in the acid leaching stage. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0043] The present invention provides a lithium battery recycling material powder, comprising a metal compound powder and a single carbon material, wherein the metal compound powder comprises at least one of the following elements: lithium, nickel, cobalt, manganese and iron; and the separation index S of the lithium battery recycling material powder satisfies 0.15m 2 / kg≤S≤43m 2 / kg, where S=W DOC ×BET, W DOC It refers to the mass percentage of soluble organic carbon in the lithium battery recycling material powder; the soluble organic carbon refers to the organic carbon that can be dissolved or dispersed in an aqueous solution with a pH of 1 to 14; BET refers to the specific surface area of ​​the lithium battery recycling material powder, in m 2 / g.

[0044] The metal compound powder includes positive electrode materials, and the positive electrode materials include at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and lithium iron phosphate; the metal compound powder is rich in valuable metals such as lithium, nickel, cobalt, manganese and iron, and its recycling has economic and environmental significance.

[0045] The elemental carbon material includes graphitized carbon, such as graphite, graphene, carbon nanotubes, etc.; in some embodiments, the elemental carbon also includes non-graphite carbon, that is, amorphous carbon, such as carbon black, hard carbon, etc.

[0046] Lithium battery recycling material powder is a powder enriched with positive electrode materials and negative electrode materials (graphite) obtained by disassembling, crushing, and sorting waste lithium batteries. The ways to recycle it include hydrometallurgy, direct regeneration, etc. Hydrometallurgy involves dispersing lithium battery recycling material powder in an acid solution for acid leaching to obtain an acid leaching solution containing valuable metal ions; some physical and chemical properties of lithium battery recycling material powder (such as particle size, specific surface area, components, etc.) have a great influence on the acid leaching process. Direct regeneration first requires the separation of metal compound powder and elemental carbon material in lithium battery recycling material powder, and then the metal compound powder is calcined with a lithium source to obtain a regenerated positive electrode material; the elemental carbon material is recycled by heat treatment, oxidation stripping, coating, etc. Some physical and chemical properties of lithium battery recycling material powder (such as surface properties, density, particle size, etc.) have a great influence on the separation efficiency of the two.

[0047] The present invention provides a lithium battery recycling material powder having a separation index S satisfying 0.15m 2 / kg≤S=W DOC ×BET≤43m 2 / kg, the lithium battery recycling material powder with a separation index in this range has good positive and negative electrode material separation efficiency and metal leaching rate.

[0048] Lower W DOC This can indirectly indicate that there is less residual organic carbon in the powder of lithium battery recycling materials. The sources of organic carbon include electrolyte that has not been completely removed, adhesive, decomposition products of electrolyte and adhesive, and external contaminated carbon sources. The residual amount and type of organic matter are related to the process parameters when obtaining the powder of lithium battery recycling materials. For example, the higher the calcination temperature and the longer the calcination time, the less residual organic carbon. For example, adding additives to promote the decomposition and gasification of organic matter will result in less residual organic carbon.

[0049] On the one hand, with lower W DOC The lithium battery recycling material powder is not easy to bubble during the acid leaching process and is conducive to improving the metal leaching rate because the organic matter dissolved during the acid leaching process (i.e. W DOC ) is equivalent to a surfactant, which makes it difficult to defoam the bubbles generated during the acid leaching process. The bubbles are easy to carry the material powder away from the liquid phase, thereby reducing the metal leaching rate. Too many bubbles are prone to bubbling and reduce production controllability. On the other hand, with a lower W DOC The lithium battery recycling material powder has good separation efficiency of positive and negative electrode materials, because the positive and negative electrode materials are usually separated by the hydrophilic and hydrophobic differences of the powder particles and the density differences. If there are too many organic substances remaining in the lithium battery recycling material powder, the hydrophilic and hydrophobic differences on the surface of the positive and negative electrode materials will be low, making it difficult to separate. DOC The lower it is, the better the quality of the lithium battery recycling material powder.

[0050] BET is the specific surface area of ​​the powder of lithium battery recycling materials. Within a certain range, the larger the BET is, the higher the metal leaching rate in the hydrometallurgical process is. However, if it is too large, it is not conducive to improving the metal leaching rate. Specifically, a BET that is too large indicates that the powder particle size is too small or the powder has a rich pore structure. A particle size that is too small will make the powder easily float on the liquid surface, reducing contact with the acid solution. Too many pores will result in a smaller density of the powder, making it easier to float on the liquid surface and reducing contact with the acid solution. In summary, BET has an appropriate range that is beneficial to improving the metal leaching rate of lithium battery recycling material powder in hydrometallurgy.

[0051] On the other hand, if BET is too small, it means that the particle size of the lithium battery recycling material powder is large and the internal pore structure of the particles is small, which is usually caused by the high degree of agglomeration of the lithium battery recycling material powder (organic residues or amorphous carbon obtained after its carbonization as a binder to bind the powder together), which will make it difficult to separate the components and the purity of the separated products is low. If BET is too large, it means that the particle size of the lithium battery recycling material powder is too small or the pore structure is too large (the more pores, the higher the degree of deviation from the true density). Since the density and particle size of graphite are usually smaller than those of the positive electrode material, if BET is too large, the difference between graphite and positive electrode material will be reduced, and the separation of positive and negative electrode materials in the lithium battery recycling material powder by density difference or mass difference will be difficult and controllable. In summary, BET has an appropriate range that is conducive to improving the separation of positive and negative electrode materials in lithium battery recycling material powder.

[0052] Because W DOC The influence of BET on the metal leaching rate and the separation efficiency of positive and negative electrode materials is the same as that of the separation index S=W. DOC ×BET comprehensively reflects the separation ability of each component in the lithium battery recycling material powder, and has the ability to meet the 0.15m 2 / kg≤S≤43m 2 / kg of lithium battery recycled material powder has good positive and negative electrode material separation efficiency and metal leaching rate.

[0053] It should be pointed out that DOC (Dissolved Organic Carbon) refers to the organic carbon content of lithium battery recycling material powder dissolved or dispersed in aqueous solution, and the aqueous solution includes aqueous solution with pH = 1~14; during the experiment, it was found that the W of lithium battery recycling material powder at different pH values DOC There is a difference, because the acid leaching of hydrometallurgy is usually carried out at a pH below 3, while the flotation separation is usually carried out at a pH greater than 7, so the W of the lithium battery recycling material powder is different. DOC The determination in each pH range is beneficial to the comprehensive evaluation of the separation index.

[0054] It should be noted that the separation index S of the lithium battery recycling material powder measured at any pH between pH 1 and 14 satisfies 0.15m 2 / kg≤S≤43m 2 / kg, are all within the protection scope defined by the present invention. For example, a lithium battery recycling material powder meets the 0.15m 2 / kg≤S≤43m 2 / kg, but does not meet the 0.15m 2 / kg≤S≤43m 2 / kg is still within the protection scope of the present invention.

[0055] In some embodiments, when the pH of the aqueous solution is ≤3, the separation index S of the lithium battery recycling material powder satisfies 2m 2 / kg≤S≤24m 2 / kg, the lithium battery recycling material powder in this range has a good metal leaching rate in the acid leaching process of hydrometallurgy, which is beneficial to improve the metal recovery rate of hydrometallurgy; the separation index S of the lithium battery recycling material powder can be 2.03m 2 / kg≤S≤10.2m 2 / kg, 10.2m 2 / kg≤S≤15m 2 / kg, 15m 2 / kg≤S≤23.95m 2 / kg, etc. or any value within a range.

[0056] In some embodiments, when the pH of the aqueous solution is ≥ 10, the separation index S of the lithium battery recycling material powder satisfies 13m 2 / kg≤S≤40m 2 / kg, the lithium battery recycling material powder in this range has good separation efficiency when separating positive and negative electrode materials by flotation, which is beneficial to improve the recycling rate of positive and negative electrode materials; the separation index S of lithium battery recycling material powder can be 13m 2 / kg≤S≤20m 2 / kg, 20m 2 / kg≤S≤26.5m 2 / kg, 26.5m 2 / kg≤S≤38.6m 2 / kg, etc. or any value within a range.

[0057] In some embodiments, the W of the lithium battery recycled material powder is DOC Less than or equal to 15‰, in this W DOC The lithium battery recycling material powder in the range has good metal leaching rate and positive and negative electrode material separation efficiency; the W of lithium battery recycling material powderDOC It can be 0~0.6‰, 0.6‰~1.7‰, 1.7‰~2.8‰, 5‰~9.5‰, 7‰~13.5‰, etc. or a value within any range.

[0058] In some embodiments, the iron content of the lithium battery recycled material powder is 10% to 30% by weight. DOC Less than 3‰; for example, the mass percentage of iron in the lithium battery recycling material powder can be 10%~15%, 15%~20%, 20%~30%, etc. or a value within any range.

[0059] In some embodiments, the mass percentage of cobalt element in the lithium battery recycling material powder is 1% to 50%. DOC 5‰~15‰; for example, the mass percentage of cobalt element in lithium battery recycling material powder can be 1%~5%, 5%~10%, 10%~30%, 30%~50%, etc. or a value within any range.

[0060] In some embodiments, when the pH of the aqueous solution is ≤3, the W of the lithium battery recycling material powder is DOC Less than 10‰.

[0061] In some embodiments, when the pH of the aqueous solution is ≥10, the W of the lithium battery recycling material powder is DOC It is 7‰~14‰.

[0062] In some embodiments, the BET of the lithium battery recycling material powder satisfies 1m 2 / g≤BET≤15m 2 / g.

[0063] In some embodiments, the iron content of the lithium battery recycling material powder is 10% to 30% by mass, and the BET of the lithium battery recycling material powder is 10 to 15 m 2 / g.

[0064] In some embodiments, the mass percentage of cobalt element in the lithium battery recycling material powder is 1% to 50%, and the BET of the lithium battery recycling material powder is 1 to 3 m 2 / g.

[0065] In some embodiments, the Dv50 of the lithium battery recycling material powder is 0.6-16 μm. The particle size of the lithium battery recycling material powder has an impact on its BET. The smaller the particle size, the larger the BET, that is, the larger the separation index S; the larger the particle size, the smaller the BET, that is, the smaller the separation index S. The Dv50 of the lithium battery recycling material powder can be 0.6-4.08 μm, 4.08-7.64 μm, 7.64-10 μm, 10-16 μm, etc. or a value in any range.

[0066] In some embodiments, the Dv10 of the lithium battery recycling material powder is 0.1~1.5μm, for example, it can be 0.1~0.73μm, 0.74~0.93μm, 1.0~1.5μm, etc. or a value within any range; the lithium battery recycling material powder within this range avoids BET being too large or too small, thereby affecting its application performance, for example, during hydrometallurgy, it can avoid excessive powder floating on the liquid surface to reduce the metal leaching rate.

[0067] In some embodiments, the Dv10 of the lithium battery recycling material powder is 0.5~5.2μm, for example, it can be 0.5~1.5μm, 1.52~2.32μm, 2.32~5.2μm, etc. or a value within any range; the lithium battery recycling material powder with Dv10 within this range avoids BET being too large or too small, thereby affecting its application performance, for example, during hydrometallurgy, it can avoid excessive powder floating on the liquid surface to reduce the metal leaching rate.

[0068] In some embodiments, the lithium mass percentage of the lithium battery recycling material powder is 0-10%. For example, the lithium mass percentage of the lithium battery recycling material powder can be 1%-3%, 3%-5%, 5%-10%, etc. or a value within any range.

[0069] The present invention provides a method for preparing the lithium battery recycling material powder in any of the above embodiments, wherein organic matter is removed as much as possible during the preparation process, and the process conditions are controlled so that the lithium battery recycling material powder has a suitable BET, so that its separation index S meets the requirements. Specifically, the following method can be used for preparation, but is not limited to the method provided in the embodiments of the present invention.

[0070] A method for preparing lithium battery recycling material powder comprises the following steps: Provide lithium battery recycling crude materials including negative electrode materials, positive electrode materials and organic matter; The recycled raw material of lithium battery is subjected to photocatalytic oxidation treatment to obtain a photo-treated intermediate; flash drying the light-treated intermediate to obtain a dry intermediate; heat-treating the dried intermediate to obtain a heat-treated intermediate; The material is cooled to below 20° C. in an inert atmosphere, crushed and sieved to obtain lithium battery recycling material powder.

[0071] In some embodiments, the positive electrode material includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium iron phosphate.

[0072] In some embodiments, the negative electrode material includes graphite.

[0073] In some embodiments, the organic matter includes a polymer compound obtained by reacting a carbon-carbon unsaturated bond and an organic solvent, the polymer compound includes but is not limited to at least one of polyvinylidene fluoride PVDF, polyacrylonitrile PAN, polyacrylic acid PAA, polyethylene PE and polypropylene PP, and the organic solvent includes but is not limited to at least one of ethylene carbonate, propylene carbonate, butylene carbonate, pentyl carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate and ethyl methyl carbonate. The polymer compound in the recycled raw material of lithium batteries is usually the main component of the adhesive and the diaphragm; the organic solvent in the recycled raw material of lithium batteries is usually the main component of the electrolyte.

[0074] The preparation method provided by the present invention combines the photocatalytic oxidation method and the heat treatment method to process the lithium battery recycling material, and controls the cooling stage of the heat-treated material, which greatly reduces the energy consumption and improves the efficiency, and obtains a low W DOC and lithium battery recycling material powder suitable for BET.

[0075] The present invention combines photocatalytic oxidation and heat treatment to treat lithium battery recycled coarse materials, aiming to remove organic matter therein under relatively mild and economical conditions and reduce W in lithium battery recycled material powder. DOC .

[0076] The photocatalytic oxidation method of the present invention utilizes ultraviolet light to irradiate a photocatalyst (such as titanium dioxide, zinc oxide, etc.). After the photocatalyst absorbs photons, the electrons in the valence band transition to the conduction band to generate electron-hole pairs. The transitioned electrons reduce the oxygen adsorbed on the surface of the photocatalyst to generate superoxide anion free radicals (·O 2 - ), the holes left behind can oxidize water adsorbed on the surface of the photocatalyst to generate hydroxyl radicals (·OH); the generated free radicals can react with organic matter adsorbed on the surface of the photocatalyst, oxidatively break its chemical bonds to degrade it; in the process of generating free radicals, the transition electrons in the photocatalyst return to the valence band. Compared with the Fenton oxidation method to degrade organic matter and recycle waste batteries, the ultraviolet light catalytic oxidation degradation method of the present invention does not require the input of chemicals or additional post-processing, and the reaction conditions are mild, which can greatly reduce costs.

[0077] However, since the oxidation method has limited ability to degrade organic matter and can only degrade polymer chains into fragments, further heat treatment is required to completely decompose the organic matter. Heat treatment after oxidation greatly improves the efficiency of heat treatment, and the temperature and time of heat treatment can be reduced.

[0078] The present invention flash evaporation and drying treatment is performed on the photo-treated intermediate. Organic matter, especially adhesive, in the lithium battery recycling crude material is degraded and loses most of its adhesive force after photo-treatment. High-speed hot air flow (hot air) during flash evaporation is used to convectively contact with the material to disperse it, and expose the organic matter on the particle surface, which is conducive to its complete elimination in the subsequent heat treatment stage; at the same time, high-speed hot air flow (hot air) is used to contact with the material to quickly evaporate the water or solvent in the material, thereby achieving rapid drying. Heat treatment is performed after drying to avoid rapid evaporation of water at high temperature to cause violent expansion or bursting, thereby avoiding an increase in specific surface area.

[0079] Photocatalytic oxidation treatment refers to irradiating lithium battery recycled raw materials with ultraviolet light in an oxygen-containing or / and water-containing environment in the presence of a photocatalyst; in some embodiments, the photocatalyst includes at least one of titanium dioxide and zinc oxide.

[0080] In some embodiments, the photocatalyst is anatase titanium dioxide.

[0081] In some embodiments, the particle size of the photocatalyst is less than 500nm, and is loaded on at least one of the following carriers including but not limited to: aluminum foil, ceramics, glass, silicon dioxide, molecular sieves and screens, in order to facilitate the separation of the phototreatment intermediate from the photocatalyst. Photocatalysts with smaller particle sizes are beneficial to increase their specific surface area, increase the active sites of the photooxidation reaction, and thus improve the efficiency of photocatalytic oxidation treatment. Since the photocatalyst is a powder material with a smaller particle size, in order to facilitate its separation from the phototreatment intermediate and the reuse of the photocatalyst, the photocatalyst is loaded on a carrier. The present invention does not limit the carrier and loading method of the photocatalyst, such as a carrier loaded with a photocatalyst in the form of a film, sheet, plate, large particles, etc.

[0082] In some embodiments, the ultraviolet light irradiation conditions include: a light wavelength of 200-400 nm and an irradiation time of 5-15 h. The shorter the light wavelength, the greater the energy, but less than 200 nm is vacuum ultraviolet and cannot be used normally in an air environment. 200-400 nm is a common wavelength range for photochemical reactions, of which 254 nm is the most commonly used wavelength in ultraviolet reaction devices. The irradiation time has an impact on the degree of degradation of organic matter. The longer the illumination time, the higher the degree of degradation.

[0083] In some embodiments, the ambient humidity of the photocatalytic oxidation treatment is maintained at 60% to 100%, and the ambient oxygen content is maintained at more than 30vt%. According to the principle, the photocatalytic oxidation treatment process needs to be carried out under oxygen-containing conditions, and water can further promote the oxidation reaction. Therefore, the higher the ambient humidity and the higher the oxygen content, the more conducive it is to the photocatalytic oxidation reaction.

[0084] In some embodiments, the inlet air temperature of the flash drying is 200-400° C., the outlet air temperature is 100-200° C., the rotation speed is 10-30 Hz, and the feed frequency is 10-30 Hz.

[0085] In some embodiments, the heat treatment is performed under negative pressure, with the pressure being -0.01 to -0.05 MPa; the negative pressure is conducive to the gasification and overflow of organic matter and amorphous carbon, while reducing the pore structure.

[0086] In some embodiments, the heat treatment temperature is 350° C. to 500° C., and the time is 0.5 to 1.5 h.

[0087] By controlling the conditions of heat treatment, including furnace pressure, oxygen content, temperature, and time, it is possible to control the BET specific surface area of ​​lithium battery recycled material powder and obtain powder in a suitable BET range.

[0088] In some embodiments, the cooling rate is 1-6°C / min. Controlling a smaller cooling rate can avoid the accumulation of internal stress of the powder particles, which is conducive to the stable shrinkage of the pore size, thereby avoiding lattice defects and particle cracking, and effectively controlling the BET of the lithium battery recycling material powder.

[0089] The material is heat treated under negative pressure, which is conducive to the gasification and overflow of organic matter and reduces the pore structure of the material after heat treatment. The cooling rate of the heat-treated material is further controlled to make it cool down at a slower rate. On the one hand, it can prevent the lithium battery recycling material powder from recombining with volatile substances in the environment to form a polluted carbon source; on the other hand, it can prevent the positive active material in the lithium battery recycling material powder from producing lattice defects and affecting regeneration; furthermore, the slower cooling rate avoids the powder from cracking due to rapid cooling, thereby increasing the porosity. The slower cooling rate is conducive to controlling the specific surface area. It is further required to reduce the temperature to below 20°C at this cooling rate, which is conducive to the stabilization and slow contraction of the pores of the powder material particles.

[0090] In some embodiments, the particle size of the lithium battery recycled coarse material is less than 1 cm.

[0091] In some embodiments, the lithium battery recycled raw material is obtained by crushing the battery waste by mechanical means such as disassembly, stamping, grinding, and shearing.

[0092] In some embodiments, battery waste includes, but is not limited to, used batteries, used battery cells, used battery rolls, pole piece waste, unqualified batteries on a production line, etc.

[0093] In some embodiments, the light portion of the battery waste, such as plastic, aluminum foil, copper foil, etc., is removed by, for example, air separation, screening, density sorting, optical sorting, etc.

[0094] In some embodiments, the larger parts of the battery waste, such as the casing, wires, and sealing plates, can be separated by manual or automatic sorting. For example, the magnetic parts can be separated by a magnetic separator, and the non-magnetic metals can be separated by an eddy current separator.

[0095] The present invention provides an application of lithium battery recycled material powder in any of the above embodiments.

[0096] The powder of lithium battery recycled material is applied to hydrometallurgy, and the hydrometallurgy step comprises: dispersing the powder of lithium battery recycled material in an acid solution to obtain an acid leaching solution containing metal ions.

[0097] In some embodiments, the post-acid leaching solution is subjected to steps including but not limited to impurity removal, extraction, precipitation and drying to obtain a product enriched in valuable metal elements, wherein the valuable metal elements include at least one of nickel, cobalt, manganese, lithium and iron.

[0098] In some embodiments, the post-acid leaching solution is subjected to steps including but not limited to impurity removal, extraction, etc. to obtain an aqueous solution enriched with metal salts; the metal salts include at least one of nickel salts, cobalt salts, manganese salts and lithium salts.

[0099] In some embodiments, the acid leaching solution is subjected to steps including but not limited to impurity removal, precipitation, carbonization, drying, etc. to obtain lithium carbonate.

[0100] The lithium battery recycled material powder is used for positive electrode material regeneration, and the steps include: using flotation separation method to enrich the positive electrode material in the lithium battery recycled material powder, adding lithium to calcine the positive electrode material to obtain regenerated positive electrode material.

[0101] Lithium battery recycled material powder is applied to graphite recycling, and the steps include: using flotation separation method to enrich graphite in lithium battery recycled material powder, and recycling the graphite.

[0102] In some embodiments, graphite is thermally treated to obtain a regenerated negative electrode material.

[0103] In some embodiments, graphite is used to prepare graphene.

[0104] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0105] Example 1 A lithium battery recycling material powder, the preparation method comprising the following steps: (1) Obtaining lithium battery recycling coarse material: The discharged waste ternary lithium-ion aluminum shell batteries are subjected to double-axis shearing crushing and single-axis crushing in sequence under nitrogen protection. The crushed materials are dried in a nitrogen atmosphere at 140-150°C for 2 hours, then broken up by a disperser, and then sieved to obtain large pieces of material (protective shell) and small pieces of material; the small pieces of material are sieved by a circular vibrating screen, and the screened material obtained is the primary lithium battery recycling coarse material; the large pieces of material are subjected to baffled air separation and linear screen air flow separation in sequence to separate the diaphragm and the aluminum shell, and the residue is subjected to single-axis crushing again and then sieved by a circular vibrating screen to obtain the screened material as the secondary lithium battery recycling coarse material; the primary lithium battery recycling coarse material and the secondary lithium battery recycling coarse material are combined to obtain the lithium battery recycling coarse material.

[0106] (2) Obtaining a photo-treated intermediate: The lithium battery recycled crude material is evenly distributed on the carrier of the photocatalytic oxidation device, and then irradiated with ultraviolet light for 10 hours.

[0107] The carrier is an aluminum foil with an active titanium dioxide coating on the surface. The active titanium dioxide is anatase titanium dioxide with a particle size of less than 500 nm. The loading amount of the active titanium dioxide on the aluminum foil is 15±2 g / m 2 .

[0108] The wavelength of the ultraviolet light is 254nm, which is provided by a 15W UVC lamp; the distance between the light source and the carrier is 30cm~50cm.

[0109] The humidity of the photocatalytic oxidation device is controlled to be 80%~90%, and the oxygen content is controlled to be 60vt%~70vt%.

[0110] (3) Obtaining a dry intermediate: placing the light-treated intermediate into a flash dryer for drying to obtain a dry intermediate; setting the inlet air temperature of the flash dryer to 300°C, the outlet air temperature to 150°C, the main engine speed to 20 Hz, and the feed frequency to 10 Hz.

[0111] (4) Obtaining a heat-treated intermediate: placing the dried intermediate in a sintering furnace for heat treatment, controlling the sintering temperature to 450°C, the heating rate to 5°C / min, the furnace pressure to -0.03 MPa, and the time to 1 h.

[0112] (5) Obtaining lithium battery recycled material powder: After the heat treatment is completed, maintain the negative pressure of the sintering furnace and set the cooling rate to 3°C / min, reduce the material temperature to 20°C, use a disperser to disperse the material, and then sieve to obtain lithium battery recycled material powder.

[0113] Example 2 A lithium battery recycling material powder, the preparation method comprising the following steps: (1) Obtaining lithium battery recycling coarse material: Disassemble the discharged waste ternary lithium-ion aluminum shell batteries to obtain battery cells; perform double-axis crushing and impact crushing on the battery cells in turn, and then use a linear screen to screen the screened material to obtain lithium battery recycling coarse material.

[0114] (2) Obtaining a light-treated intermediate: Control the humidity of the photocatalytic oxidation device to 60%-70%, and the oxygen content to 60vt%-70vt%. Others are the same as in Example 1.

[0115] (3) Obtaining a dried intermediate: Same as Example 1.

[0116] (4) Obtaining a heat-treated intermediate: controlling the sintering temperature to 400°C, the heating rate to 5°C / min, the furnace pressure to -0.05 MPa, and the rest to be the same as in Example 1.

[0117] (5) Obtaining lithium battery recycled material powder: maintaining negative pressure in the sintering furnace and setting the cooling rate to 1°C / min, and the rest is the same as in Example 1.

[0118] Example 3 A lithium battery recycling material powder, the preparation method comprising the following steps: (1) Obtaining lithium battery recycled crude material: the same as in Example 1.

[0119] (2) Obtaining a photo-treated intermediate: The lithium battery recycled crude material is evenly distributed on the carrier of the photocatalytic oxidation device, and then irradiated with ultraviolet light for 5 hours.

[0120] The carrier is a glass plate with an active zinc oxide coating on the surface, the active zinc oxide is active zinc oxide with a particle size of less than 500 nm, and the loading amount of the active zinc oxide on the glass plate is 25±2 g / m 2 .

[0121] The wavelength of the ultraviolet light is 254nm, which is provided by a 15W UVC lamp; the distance between the light source and the carrier is 30cm~50cm.

[0122] The humidity of the photocatalytic oxidation device is controlled to be 60%~70%, and the oxygen content is controlled to be 30vt%~40vt%.

[0123] (3) Obtaining a dry intermediate: placing the light-treated intermediate into a flash dryer for drying to obtain a dry intermediate; setting the inlet air temperature of the flash dryer to 300°C, the outlet air temperature to 150°C, the rotation speed to 10 Hz, and the feed frequency to 30 Hz.

[0124] (4) Obtaining a heat-treated intermediate: placing the dried intermediate in a sintering furnace for heat treatment, controlling the sintering temperature to 350°C, the heating rate to 5°C / min, the furnace pressure to -0.01 MPa, and the time to 1 h.

[0125] (5) Obtaining lithium battery recycled material powder: maintaining negative pressure in the sintering furnace and setting the cooling rate to 6°C / min, and the rest is the same as in Example 1.

[0126] Example 4 A lithium battery recycling material powder, the preparation method comprising the following steps: (1) Obtaining lithium battery recycling coarse material: The discharged waste ternary lithium-ion soft-pack batteries are subjected to double-axis crushing and reamer crushing in sequence under nitrogen protection. The crushed materials are dried in a nitrogen atmosphere at 140-150°C for 2 hours, and then cyclone-conveyed to a vibrating screen for screening. The screened material is primary lithium battery recycling coarse material; the screened material is further subjected to magnetic separation to obtain secondary lithium battery recycling coarse material, and the primary lithium battery recycling coarse material and the secondary lithium battery recycling coarse material are combined to obtain lithium battery recycling coarse material.

[0127] (2) Obtaining a photo-treated intermediate: Irradiating it with ultraviolet light for 15 h. The rest is the same as in Example 1.

[0128] (3) Obtaining a dried intermediate: Same as Example 1.

[0129] (4) Obtaining a heat-treated intermediate: The sintering temperature was controlled to be 400°C and the furnace pressure was controlled to be -0.01 MPa. The other conditions were the same as those in Example 1.

[0130] (5) Obtaining lithium battery recycled material powder: maintaining negative pressure in the sintering furnace and setting the cooling rate to 6°C / min, and the rest is the same as in Example 1.

[0131] Example 5 A lithium battery recycling material powder, the preparation method comprising the following steps: (1) Obtaining lithium battery recycling crude material: The process is the same as that in Example 2, but the waste ternary lithium-ion aluminum shell batteries used are different.

[0132] (2) Obtaining a light-treated intermediate: Irradiating it with ultraviolet light for 8 h. The rest is the same as in Example 1.

[0133] (3) Obtaining a dry intermediate: placing the light-treated intermediate into a flash dryer for drying to obtain a dry intermediate; setting the flash dryer's inlet air temperature to 300°C, outlet air temperature to 100°C, rotation speed to 30 Hz, and feed frequency to 30 Hz.

[0134] (4) Obtaining a heat-treated intermediate: The sintering temperature was controlled to be 350°C and the furnace pressure was controlled to be -0.03 MPa. The other conditions were the same as those in Example 1.

[0135] (5) Obtaining lithium battery recycled material powder: maintaining negative pressure in the sintering furnace and setting the cooling rate to 6°C / min, and the rest is the same as in Example 1.

[0136] Example 6 A lithium battery recycling material powder, the preparation method comprising the following steps: (1) Obtaining lithium battery recycling coarse material: The discharged waste ternary lithium-ion aluminum shell batteries are subjected to double-axis shearing and single-axis crushing in sequence under nitrogen protection. The crushed materials are dried in a nitrogen atmosphere at 140-150°C for 2 hours, then broken up with a breaker, and then sieved to obtain large pieces of material (protective shell) and small pieces of material; the small pieces of material are sieved with a circular vibrating screen, and the screened material obtained is the lithium battery recycling coarse material.

[0137] (2) Obtaining a photo-treated intermediate: The lithium battery recycled crude material is evenly distributed on the carrier of the photocatalytic oxidation device, and then irradiated with ultraviolet light for 12 hours.

[0138] The carrier is a glass plate with an active zinc oxide coating on the surface, the active zinc oxide is active zinc oxide with a particle size of less than 500 nm, and the loading amount of the active zinc oxide on the glass plate is 25±2 g / m 2 .

[0139] The wavelength of the ultraviolet light is 254nm, which is provided by a 15W UVC lamp; the distance between the light source and the carrier is 30cm~50cm.

[0140] The humidity of the photocatalytic oxidation device is controlled to be 80%~90%, and the oxygen content is controlled to be 60vt%~70vt%.

[0141] (3) Obtaining a dry intermediate: placing the light-treated intermediate into a flash dryer for drying to obtain a dry intermediate; setting the flash dryer's inlet air temperature to 400°C, outlet air temperature to 200°C, rotation speed to 10 Hz, and feed frequency to 20 Hz.

[0142] (4) Obtaining a heat-treated intermediate: placing the dried intermediate in a sintering furnace for heat treatment, controlling the sintering temperature to 500°C, the heating rate to 5°C / min, the furnace pressure to -0.02 MPa, and the time to 1 h.

[0143] (5) Obtaining lithium battery recycled material powder: the same as in Example 1.

[0144] Example 7 A lithium battery recycling material powder, the preparation method comprising the following steps: (1) Obtaining lithium battery recycling coarse material: The discharged waste lithium iron phosphate batteries are crushed in two stages under nitrogen protection (the first stage is a double-axis shear crusher and the second stage is a single-axis shear crusher). The crushed materials are dried in a nitrogen atmosphere at 140-150°C for 2 hours, then broken up with a breaker, and then sieved to obtain large pieces of material (protective shell) and small pieces of material; the small pieces of material are sieved with a circular vibrating screen, and the screened material obtained is the lithium battery recycling coarse material.

[0145] (2) Obtaining a photo-treated intermediate: The lithium battery recycled crude material is evenly distributed on the carrier of the photocatalytic oxidation device, and then irradiated with ultraviolet light for 12 hours.

[0146] The carrier is a glass plate with an active zinc oxide coating on the surface, the active zinc oxide is active zinc oxide with a particle size of less than 500 nm, and the loading amount of the active zinc oxide on the glass plate is 25±2 g / m 2 .

[0147] The wavelength of the ultraviolet light is 254nm, which is provided by a 15W UVC lamp; the distance between the light source and the carrier is 30cm~50cm.

[0148] The humidity of the photocatalytic oxidation device is controlled to be 80%~90%, and the oxygen content is controlled to be 60vt%~70vt%.

[0149] (3) Obtaining a dry intermediate: placing the light-treated intermediate into a flash dryer for drying to obtain a dry intermediate; setting the flash dryer's inlet air temperature to 200°C, outlet air temperature to 100°C, rotation speed to 20 Hz, and feed frequency to 10 Hz.

[0150] (4) Obtaining a heat-treated intermediate: placing the dried intermediate in a sintering furnace for heat treatment, controlling the sintering temperature to 500°C, the heating rate to 5°C / min, the furnace pressure to -0.05 MPa, and the time to 0.5 h.

[0151] (5) Obtaining lithium battery recycling material powder: After the heat treatment is completed, maintain the negative pressure of the sintering furnace and set the cooling rate to 4°C / min, reduce the material temperature to 20°C, and use a disintegrator to disperse the material, and then sieve to obtain lithium battery recycling material powder.

[0152] Example 8 A lithium battery recycling material powder, the preparation method comprising the following steps: (1) Obtaining lithium battery recycled crude material: the same as in Example 7.

[0153] (2) Obtaining a photo-treated intermediate: The lithium battery recycled crude material is evenly distributed on the carrier of the photocatalytic oxidation device, and then irradiated with ultraviolet light for 10 hours.

[0154] The carrier is an aluminum foil with an active titanium dioxide coating on the surface. The active titanium dioxide is anatase titanium dioxide with a particle size of less than 500 nm. The loading amount of the active titanium dioxide on the aluminum foil is 15±2 g / m 2 .

[0155] The wavelength of the ultraviolet light is 254nm, which is provided by a 15W UVC lamp; the distance between the light source and the carrier is 30cm~50cm.

[0156] The humidity of the photocatalytic oxidation device is controlled to be 60%~70%, and the oxygen content is controlled to be 30vt%~40vt%.

[0157] (3) Obtaining a dried intermediate: Same as Example 7.

[0158] (4) Obtaining a heat-treated intermediate: controlling the sintering temperature to 450°C and the sintering time to 1 h, and the rest being the same as in Example 6.

[0159] (5) Obtaining lithium battery recycled material powder: the same as Example 7.

[0160] Example 9 A lithium battery recycling material powder, the preparation method comprising the following steps: (1) Obtaining lithium battery recycled crude material: the same as in Example 7.

[0161] (2) Obtaining a photo-treated intermediate: The lithium battery recycled crude material is evenly distributed on the carrier of the photocatalytic oxidation device, and then irradiated with ultraviolet light for 15 hours.

[0162] The carrier is an aluminum foil with an active titanium dioxide coating on the surface. The active titanium dioxide is anatase titanium dioxide with a particle size of less than 500 nm. The loading amount of the active titanium dioxide on the aluminum foil is 15±2 g / m 2 .

[0163] The wavelength of the ultraviolet light is 254nm, which is provided by a 15W UVC lamp; the distance between the light source and the carrier is 30cm~50cm.

[0164] The humidity of the photocatalytic oxidation device is controlled to be 60%~70%, and the oxygen content is controlled to be 60vt%~70vt%.

[0165] (3) Obtaining a dried intermediate: Same as Example 7.

[0166] (4) Obtaining a heat-treated intermediate: controlling the sintering temperature to 450°C, the furnace pressure to -0.01 MPa, and the sintering time to 1.5 h. Other conditions are the same as those in Example 7.

[0167] (5) Obtaining lithium battery recycled material powder: the same as Example 7.

[0168] Example 10 The difference from Example 1 is that the irradiation time in step (2) is 15 h.

[0169] Embodiment 11 The difference from Example 1 is that the irradiation time in step (2) is 5 h.

[0170] Example 12 The difference from Example 1 is that the furnace pressure in step (4) is -0.01 MPa.

[0171] Embodiment 13 The difference from Example 1 is that the furnace pressure in step (4) is -0.05 MPa.

[0172] Embodiment 14 The difference from Example 1 is that the cooling rate in step (5) is 1°C / min.

[0173] Embodiment 15 The difference from Example 1 is that the cooling rate in step (5) is 6°C / min.

[0174] Example 16 The difference from Example 1 is that step (3) is not performed, that is, the photo-treated intermediate is directly subjected to heat treatment.

[0175] Embodiment 17 The difference from Example 1 is that step (2) is not performed, that is, step (3) is directly performed on the lithium battery recycled crude material obtained in step (1).

[0176] Embodiment 18 A lithium battery recycling material powder, the preparation method comprising the following steps: (1) Obtaining coarse recycled lithium battery materials: Disassemble the discharged waste ternary lithium-ion aluminum shell batteries to obtain positive electrode sheets, crush and grade the positive electrode sheets, and then sieve them to obtain coarse recycled lithium battery materials.

[0177] Steps (2) to (5) are the same as those in Example 1.

[0178] Embodiment 19 A lithium battery recycling material powder, the preparation method comprising the following steps: (1) Obtaining lithium battery recycling coarse material: Disassemble the discharged waste lithium iron phosphate aluminum shell batteries to obtain positive electrode plates, crush and grade the positive electrode plates, and then sieve them to obtain lithium battery recycling coarse material.

[0179] (2)~(3) are the same as in Example 7.

[0180] (4) Obtaining a heat-treated intermediate: placing the dried intermediate in a sintering furnace for heat treatment, controlling the sintering temperature to 700°C, the heating rate to 5°C / min, the furnace pressure to 0.02 MPa, and the time to 1.5 h.

[0181] (5) Same as Example 7.

[0182] Embodiment 20 A lithium battery recycling material powder, the preparation method comprising the following steps: (1)~(2) are the same as in Example 7.

[0183] (3) Obtaining a ball-milled intermediate: Place the phototreated intermediate in a ball mill and ball-mill for 1 h to obtain a ball-milled intermediate.

[0184] (4) Obtaining a heat-treated intermediate: placing the ball-milled intermediate in a sintering furnace for heat treatment, controlling the sintering temperature to 500°C, the heating rate to 5°C / min, the furnace pressure to -0.05 MPa, and the time to 0.5 h.

[0185] (5) Obtaining lithium battery recycling material powder: After the heat treatment is completed, maintain the negative pressure of the sintering furnace and set the cooling rate to 10°C / min, reduce the material temperature to 20°C, and use a disintegrator to disperse the material, and then sieve to obtain lithium battery recycling material powder.

[0186] Comparative Example 1 The difference from Example 1 is that the heat treatment temperature in step (4) is 900° C. and the furnace pressure is -0.07 MPa.

[0187] Comparative Example 2 The difference from Example 1 is that step (4) is heat treated at normal pressure at a temperature of 300°C.

[0188] Comparative Example 3 The difference from Example 1 is that the heat-treated intermediate in step (4) is exposed to air at room temperature (25° C.) for natural cooling.

[0189] Ingredients Description: The battery waste used to obtain lithium battery recycling raw materials are not necessarily the same. The differences include battery cells, the type of positive electrode material in the positive electrode sheet, the ratio of positive electrode material to negative electrode material, etc.

[0190] The raw materials of the lithium iron phosphate waste batteries used in Examples 7 to 9 are the same, and the raw materials of the ternary waste batteries used in Examples 10 to 15 and Comparative Examples 1 to 3 are the same as those in Example 1.

[0191] Photocatalytic oxidation treatment instructions: The present invention does not limit the preparation method of the carrier of the photocatalytic oxidation device. Any method of loading titanium dioxide or zinc oxide with photocatalytic oxidation activity on a carrier, which can easily separate the phototreated intermediate from the carrier and recycle the carrier, can achieve the purpose of the present invention.

[0192] The preparation method of the glass plate loaded zinc oxide carrier includes but is not limited to: weighing a soluble zinc salt and dissolving it in anhydrous ethanol, adding a complexing agent (diethanolamine, citric acid, ethanolamine, etc.) and stirring to obtain a sol, and after aging, the sol is loaded on a glass sheet by an immersion pulling method, and finally sintering at 450-600°C for 30-60 minutes to obtain the carrier.

[0193] Taking Example 1 as an example, the preparation method of the carrier of the photocatalytic oxidation device includes: weighing butyl titanate and dissolving it in anhydrous ethanol, adding diethanolamine and stirring for 2 hours, then adding 20wt% acetylacetone aqueous solution, and continuing to stir for 1 hour to obtain titanium dioxide sol. The titanium dioxide sol is loaded on an aluminum foil with a thickness of 0.2 mm by an immersion pulling method, and finally sintered at 500°C to obtain the carrier, and the pulling speed and number and the concentration of the titanium dioxide sol are controlled to control the loading capacity of the carrier.

[0194] Performance testing method: Test Example 1: W DOC The test includes the following steps: ① Weigh 100.0±0.01g of the sample to be tested and place it in a 500mL extraction bottle. Use a measuring cylinder to measure 300mL (V 0 ) Add the aqueous solution into the extraction bottle, cover the inner cover tightly, tighten the bottle cap and fix it vertically on the water bath constant temperature oscillator; ② Set the water temperature of the water bath constant temperature oscillator to 25°C, the oscillation frequency to 110 times / min, the amplitude to 20mm, start the instrument, and oscillate for 60 minutes; ③After the shaking is completed, remove the extraction bottle, shake the sample to be tested, filter it with slow quantitative filter paper, and the filtrate is used to test W DOC ; ④ Remove a certain volume (V 1 ) The filtrate was placed in a 100 mL volumetric flask, acidified to pH ≤ 2 and diluted to the mark to obtain a volume of V 2 The diluted liquid is then aerated to remove inorganic carbon and then introduced into the high temperature oxidation furnace of the TOC analyzer to test the concentration C.

[0195] W DOC = ; In the formula, C 1 is the concentration of the sample to be tested by the TOC analyzer, mg / L; C 0is the sample concentration of the blank sample TOC analyzer test, mg / L; V 2 is the constant volume of the diluent, mL; V 1 is the volume of the filtrate removed in step ④, mL; V 0 is the volume of the aqueous solution initially added, L; m is the mass of the sample to be tested, g. The blank sample refers to the test performed in step ① without adding the sample to be tested.

[0196] The aqueous solution in step ① is selected from one of pH=2, pH=7 and pH=10, the aqueous solution of pH=2 is prepared by dissolving 98% sulfuric acid in pure water, the aqueous solution of pH=10 is prepared by dissolving sodium hydroxide in pure water, and the aqueous solution of pH=7 is pure water.

[0197] Test Example 2: The specific surface area BET was tested according to GB / T 19587-2004.

[0198] Test Example 3: The mass percentage content of Ni, Co, Mn, Li and Fe metal elements in lithium battery recycled material powder was tested in accordance with YS / T1342.1-2019, YS / T1342.2-2019, YS / T1342.3-2019, YS / T1342.4-2019 and YS / T 1028.1-2015.

[0199] Test Example 4: Metal leaching efficiency test, including the following steps: The lithium battery recycled material powder to be tested was put into the acid leaching solution (a sulfuric acid solution with a pH of 0.5~1 and a hydrogen peroxide volume concentration of 20%) at a solid-liquid ratio of 1g:4g, stirred at 80°C for 6h, and the solid-liquid separation was performed to obtain the acid leaching liquid. The metal concentration in the acid leaching liquid was determined by ICP-OES, and the metal leaching rate was calculated.

[0200] Metal leaching rate = ×100%; Wherein, the metal leaching rate is the ratio of the total mass of the metal elements (including at least one of Ni, Co, Mn, Fe and Li) in the leached solution to the total mass of the metal elements in the lithium battery recycling material powder; , are the concentrations of Ni, Co, Mn, Li and Fe in the acid leaching solution, g / L; V is the volume of the acid leaching solution, L; is the feeding amount of lithium battery recycling material powder, g; , They are the mass percentages of Ni, Co, Mn, Li and Fe in the lithium battery recycled material powder, %.

[0201] The chemical reactions that occur during acid leaching are as follows: 2LiFePO4 +H 2 SO 4 +H 2 O 2 →Li 2 SO 4 +2FePO 4 ↓+2H 2 O; 2Li(Ni x Co y Mn 1-x-y ) 2 +3H 2 SO 4 +3H 2 O 2 →Li 2 SO 4 +2xNiSO 4 +2yCoSO 4 +2(1-xy)MnSO 4 +6H 2 O+2O 2 ↑; 2Li(Co / Mn / Ni)O 2 +3H 2 SO 4 +H 2 O 2 →Li 2 SO 4 +2(Co / Mn / Ni)SO 4 +4H 2 O+O 2 ↑.

[0202] Test Example 5: Flotation separation efficiency test, including the following steps: In the XFG hanging trough flotation machine, the lithium battery recycling material powder and water are mixed and slurried, and NaOH is added to adjust the pH to 9.5-10 to obtain the first slurry with a slurry concentration of 40 g / L; the collector n-dodecane is added to the first slurry at 250 g / L for 3 minutes, and then the foaming agent methyl isobutyl carbinol MIBC is added at 180 g / L for 1 minute, and the air valve is opened to control the inflation volume to 0.8 L / min, and the stirring speed is 1800 r / min. After one roughing and two scavenging, the slurry underflow and foam product (including roughing foam and scavenging foam) are obtained; the slurry underflow is separated from the solid and liquid, and dried to obtain the metal recovery powder enriched with the positive electrode material; the foam product is separated from the solid and liquid, and dried to obtain the enriched graphite recovery powder.

[0203] The metal recovery rate and separation accuracy were calculated by the following formula to evaluate the flotation separation efficiency: Metal recovery rate = ×100%; Separation accuracy = ×100%; In the formula, and They are the input of lithium battery recycled material powder, the output of metal recycled powder and graphite recycled powder, They are respectively the total content percentage of metal elements in lithium battery recycled material powder, metal recycled powder and graphite recycled powder, and the metal elements include at least one of Ni, Co, Mn, Fe and Li.

[0204] Test Example 6: The particle size of lithium battery recycled material powder was tested in accordance with GB / T 19077.1-2016.

[0205] The test results of the lithium battery recycled material powders obtained in the examples and comparative examples are shown in Table 1, Table 2 and Table 3.

[0206] Table 1

[0207] Table 2

[0208] Table 3

[0209] Comprehensive analysis of Tables 1 to 3 shows that the lithium battery recycling material powder provided by the embodiment of the present invention has better metal leaching rate and flotation separation efficiency than the comparative example.

[0210] Comparison of Examples 1 to 3 shows that the separation index S of Example 2 at different pH values ​​is consistent with 0.15m 2 / kg≤S≤43m 2 / kg, but due to the small BET of lithium battery recycled material powder, the S at pH = 10 exceeds the optimal range (13m 2 / kg≤S≤40m 2 / kg), which ultimately leads to a decrease in its flotation separation efficiency. The reason is that the BET of Example 2 is smaller, indicating that there are more agglomerates in the lithium battery recycling material powder, and the agglomerates have fewer pores, which leads to a decrease in the separation rate of positive and negative electrode materials. Although the separation index S of Example 3 at different pH values ​​meets the 0.15m 2 / kg≤S≤43m 2 / kg, but due to the BET and W DOC The larger the pH value, the greater the S value at pH = 2. 2 / kg≤S≤24m 2 / kg), which ultimately leads to a decrease in its metal leaching rate. The reason is that a larger BET indicates a smaller particle size or higher porosity of the lithium battery recycling material powder, combined with a larger W DOC , resulting in the powder tending to float on the liquid surface during the hydrometallurgical process, which reduces the leaching efficiency. The separation index of Example 1 meets the preferred range at both low pH and high pH, ​​and thus has good leaching efficiency and flotation separation efficiency.

[0211] W of Examples 1, 2, and 4 DOC At a similar level, but with different BET, it can be seen from the results that with the increase of BET, the metal leaching of lithium battery recycling material powder first increases and then decreases. The reason is that: BET is too large, which causes the lithium battery recycling material powder to float on the liquid surface and is difficult to be completely infiltrated by the acid leaching solution. BET is too small, indicating that the lithium battery recycling material powder is seriously agglomerated. Both lead to a decrease in leaching efficiency during the hydrometallurgical process. Therefore, BET is too large or too small, which is not conducive to improving the metal leaching rate; with the increase of BET, the metal recovery rate and separation accuracy of lithium battery recycling material powder first increase and then decrease. The reason is that BET is too large, indicating that the particle size of the powder particles is too small or the porosity is too high, resulting in a smaller density difference, and the metal oxide powder is more likely to adhere to the bubbles to become a bubble product, resulting in a decrease in separation accuracy; BET is too small, indicating that the lithium battery recycling material powder is seriously agglomerated, and the graphite powder and the metal compound powder are tightly combined and difficult to separate, resulting in a decrease in separation effect, so the metal recovery rate decreases.

[0212] The BET of Examples 3 and 4 are at similar levels, but have different W DOC From the results, we can see that as W DOC With the increase of , the metal leaching rate and flotation separation efficiency of lithium battery recycling material powder both decrease. The reason is that: the more residual organic matter in the lithium battery recycling material powder, the lower the difference in water wettability between the metal compound and the graphite particle surface, thereby reducing the flotation efficiency; on the other hand, the residual organic matter in the lithium battery recycling material powder is dissolved as a surfactant during the acid leaching process, which makes it difficult to eliminate the bubbles generated during the leaching process, and even the metal compound powder particles adhere to the surface of the bubbles, making it impossible to contact with the acid leaching solution for reaction. Therefore, W DOC The larger the value, the lower the metal leaching efficiency.

[0213] Comparative Example 1 has lower BET and W than Example 1. DOC , and BET is lower than the preferred range, so that the separation index S exceeds the range of the present invention, and thus has a lower metal leaching rate and flotation separation efficiency. Comparative Example 1 illustrates the process of controlling the obtained lithium battery recycling material powder, which can effectively control its BET and W DOCThe heat treatment process of Comparative Example 1 uses a higher temperature and a lower negative pressure, resulting in a higher degree of removal of organic matter in the lithium battery recycling material powder. Due to the high temperature, the metal compound powder even undergoes grain boundary fusion, which results in an increase in the particle size of the material powder, a decrease in porosity, and a decrease in BET.

[0214] Comparative Example 2 uses low temperature (300°C) and normal pressure to heat treat the dried intermediate, resulting in an increase in the residual organic matter in the lithium battery recycling material powder. The residual organic matter is equivalent to the binder that binds the positive and negative electrode materials together to form a tight agglomerate; therefore, Comparative Example 2 has a lower BET and a higher W than Example 1. DOC , so that its separation index S is beyond the scope of the present invention, thus having a lower acid leaching rate and flotation separation efficiency.

[0215] Examples 1, 10, 11, and 17 are lithium battery recycling material powders obtained under different irradiation times. As the irradiation time increases, the BET of the lithium battery recycling material powder increases. DOC The overall level decreases because: the longer the irradiation time, the higher the degree of decomposition of organic matter, thereby preventing the residual organic matter from adhering to the lithium battery recycling material powder particles, thereby increasing BET. Example 17 was not subjected to light treatment, so it has a smaller BET and a larger W DOC , resulting in the separation index S exceeding the preferred range of the present invention when pH=2, thus having a lower metal leaching rate. The metal leaching rate of Example 10 is lower than that of Example 1, but the separation efficiency is higher. The reason is that: the BET of Example 10 is larger, indicating that its particle size is smaller or the porosity is higher, and it tends to float on the liquid surface, thus resulting in a lower metal leaching rate; but because its organic matter is removed more thoroughly (i.e., W DOC The lower the particle size, the greater the difference in surface wettability between the metal compound powder and the graphite powder, and thus the better the separation effect during flotation.

[0216] Examples 1, 12, and 13 are lithium battery recycling material powders obtained by heat treatment under different pressures. As the pressure decreases (negative pressure increases), BET gradually increases. DOC The reason is that the negative pressure during the heat treatment process can promote the gasification of organic matter, discharge the gas from the pores, and reduce the adhesion of organic matter to powder particles.

[0217] Examples 1, 14, and 15 are lithium battery recycling material powders obtained at different cooling rates. As the cooling rate increases, the BET of the lithium battery recycling material powder increases. DOCThe change is not big, because: the cooling speed is too fast, resulting in residual stress inside the particles, which leads to particle rupture, and the rupture leads to increased particle porosity, which increases the specific surface area. In comparative example 3, the cooling process of the heat-treated intermediate is not controlled, and the heat-treated monomer is instantly exposed to cold air. Due to the residual stress, the material has internal cracks, which increases the BET; in addition, the organic matter in the environment (including air and organic matter vaporized during the heat treatment process) quickly condenses and adheres to the surface of the powder particles, which leads to W DOC Increase, the separation index S at pH = 10 is greater than 40m 2 / kg, its metal leaching rate and flotation separation efficiency are lower than those in Example 1.

[0218] Example 16 The light-treated intermediate was heat-treated without flash drying, and the BET of the obtained lithium battery recycling material powder was slightly reduced. DOC Increase; the reason is that the light-treated intermediates are dispersed without flash drying, resulting in the inability to fully expose the organic matter, which is not conducive to its decomposition during the heat treatment process, so W DOC Compared with Example 1, the BET of the powder of the lithium battery recycling material of Example 16 is slightly smaller than that of Example 1 due to the lack of dispersion. At the same time, the light-treated intermediate is dried without the flash drying process, which causes the water in the powder particles to evaporate rapidly at high temperature during the heat treatment, causing violent expansion or bursting, resulting in an increase in its BET. Under these two trends, the BET of the lithium battery recycling material powder of Example 16 is slightly smaller than that of Example 1. DOC Larger than Example 1.

[0219] In Example 18, the raw material used to obtain the lithium battery recycling raw material is the positive electrode sheet. The organic matter content in the positive electrode sheet is less than that in the aluminum shell battery as a whole. Therefore, the W of the obtained lithium battery recycling material powder is DOC Small. Because it does not contain negative electrode material graphite and W DOC The metal leaching rate of lithium battery recycled material powder is high, and it can be directly used for positive electrode material regeneration without flotation separation. However, since the battery needs to be carefully disassembled to obtain the positive electrode sheet, it is difficult to mass produce in industry.

[0220] Example 19 also uses the positive electrode plate as the crushing object to obtain lithium battery recycling coarse material, so the lithium battery recycling material powder W DOC It is lower than that of Examples 7 to 9, but because the heat treatment temperature is high and it is carried out under pressure, the positive electrode material undergoes grain boundary fusion, so the BET of the obtained lithium battery recycling material powder is low. Therefore, the separation index S is lower than the preferred range when pH ≤ 3, and its metal leaching rate is lower than that of Examples 7 to 9.

[0221] In Example 20, the ball milling process was used instead of the flash drying process, and the cooling rate was 10°C / min. The BET of the obtained lithium battery recycling material powder was larger than that of Examples 7 to 9, but W DOC There is little difference, so the separation index S is larger, higher than the preferred range when pH ≤ 3, so the metal leaching rate is lower than that of Examples 7 to 9, but the separation index S at pH = 10 is still in the preferred range, so the flotation separation efficiency does not decrease much.

[0222] In summary, the separation index S of the lithium battery recycling material powder provided by the present invention meets 0.15m 2 / kg≤S≤43m 2 / kg, with good metal leaching rate and flotation separation efficiency of positive and negative electrode materials. In addition, the preparation method provided by the present invention can obtain a separation index S at different pH values ​​that meets 0.15m 2 / kg≤S≤43m 2 / kg of lithium battery recycled material powder, and the separation index S of the material can be regulated by adjusting the process parameters in the preparation method, thereby regulating the application performance of the lithium battery recycled material powder.

[0223] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A lithium battery recycling material powder, characterized in that: The invention comprises a metal compound powder and a single carbon material, wherein the metal compound powder comprises at least one of the following elements: lithium, nickel, cobalt, manganese and iron; and the separation index S of the lithium battery recycling material powder satisfies 0.15m 2 / kg≤S≤43m 2 / kg, where S=W DOC ×BET, W DOC It refers to the mass percentage of soluble organic carbon in the lithium battery recycling material powder; the soluble organic carbon refers to the organic carbon that can be dissolved or dispersed in an aqueous solution with a pH of 1 to 14; BET refers to the specific surface area of ​​the lithium battery recycling material powder, in m 2 / g.

2. The lithium battery recycling material powder according to claim 1, characterized in that: The lithium battery recycling material powder meets at least one of the following characteristics 1 to 4: Feature 1: When the pH of the aqueous solution is ≤3, the separation index S of the lithium battery recycling material powder satisfies 2m 2 / kg≤S≤24m 2 / kg; Feature 2: When the pH of the aqueous solution is ≥10, the separation index S of the lithium battery recycling material powder satisfies 13m 2 / kg≤S≤40m 2 / kg; Feature 3: W of the lithium battery recycling material powder DOC Less than or equal to 15‰; Feature 4: The BET of the lithium battery recycling material powder meets 1m 2 / g≤BET≤15m 2 / g.

3. The lithium battery recycling material powder according to claim 1 or 2, characterized in that: The iron content of the lithium battery recycling material powder is 10% to 30% by mass, and the BET of the lithium battery recycling material powder is 10 to 15 m 2 / g.

4. The lithium battery recycling material powder according to claim 1 or 2, characterized in that: The mass percentage of cobalt element in the lithium battery recycling material powder is 1% to 50%, and the BET of the lithium battery recycling material powder is 1 to 3m 2 / g.

5. The lithium battery recycling material powder according to claim 4, characterized in that: The Dv10 of the lithium battery recycling material powder is 0.1-1.5 μm.

6. The lithium battery recycling material powder according to claim 4, characterized in that: The Dv10 of the lithium battery recycling material powder is 0.5~5.2μm.

7. The lithium battery recycling material powder according to claim 1 or 2, characterized in that: The lithium element mass percentage of the lithium battery recycling material powder is 0-10%.

8. A method for preparing lithium battery recycling material powder according to any one of claims 1 to 7, characterized in that: The following steps are involved: Provide lithium battery recycling crude materials including negative electrode materials, positive electrode materials and organic matter; The recycled raw material of lithium battery is subjected to photocatalytic oxidation treatment to obtain a photo-treated intermediate; flash drying the light-treated intermediate to obtain a dry intermediate; heat-treating the dried intermediate to obtain a heat-treated intermediate; The material is cooled to below 20° C. in an inert atmosphere, crushed and sieved to obtain lithium battery recycling material powder.

9. An application of the lithium battery recycling material powder as claimed in any one of claims 1 to 7, characterized in that: The lithium battery recycling material powder is applied to hydrometallurgy, and the hydrometallurgy step comprises: dispersing the lithium battery recycling material powder in an acid solution to obtain an acid-leached liquid containing metal ions.

10. An application of the lithium battery recycling material powder as claimed in any one of claims 1 to 7, characterized in that: The lithium battery recycled material powder is used for positive electrode material regeneration, and the steps include: using a flotation separation method to enrich the positive electrode material in the lithium battery recycled material powder, adding lithium to the positive electrode material and calcining it to obtain a regenerated positive electrode material.

Citation Information

Patent Citations

  • Process for recovering carbon materials of battery cathode

    CN101154757A

  • A method of capturing CO2 in a heat-engine plant by using waste lithium battery cathode materials

    CN102657994A

  • Disposal method for waste battery material

    JP2013120709A

  • Method for recycling spent lithium metal polymer rechargeable batteries and related materials

    US20040028585A1

Cited By

  • Method for recovering anode material aluminum foil of waste lithium ion battery

    CN120905535A

  • Battery black powder and preparation method and application thereof

    CN121282414A

  • Battery black powder, and preparation method and application thereof

    CN121282414B

  • Recycled lithium-ion battery material powder, preparation method therefor, and application thereof

    WO2026194240A1